Disaggregating the headquarters: Implications for overseas R&D subsidiaries' reporting and the subsidiaries' knowledge-sharing patterns - Kazuhiro Asakawa (Journal of Organization Design, 2020)
This study explores the relations between the different parts of headquarters (HQ) to which subsidiaries report and the knowledge-sharing patterns of subsidiaries in multinational corporations (MNCs). Despite the growing interest in the disaggregation of HQ, little is known about how subsidiaries' reporting relationships with different parts of HQ are associated with the knowledge-sharing patterns of subsidiaries. Based on this motivation, we disaggregated HQ into different parts, i.e., corporate R&D HQ, top management, divisional HQ, and regional HQ, and explored how knowledge-sharing patterns of overseas R&D subsidiaries vary according to the different parts of the HQ to which they report. We found that subsidiaries reporting to corporate R&D HQ show the highest level of external knowledge sharing (EKS), while those reporting to divisional HQ show the lowest level; in addition, subsidiaries reporting to top management show the highest level of internal knowledge sharing (IKS), while those reporting to regional HQ show the lowest level. The study implies that the knowledge-sharing patterns of overseas R&D subsidiaries in MNCs cannot be fully understood without examining the subsidiaries' reporting relationships with differing parts of the HQ.
Keywords: 650; Corporate R&D HQ; Divisional HQ; Regional HQ; Top management; Reporting relations; Knowledge sharing